A Case of Ameloblastic Fibroodontoma Extending Maxillary Sinus with Erupted Tooth: Is Transcanine Approach with Alveolectomy Feasible?. (6th November 2016) - Aslıer, Mustafa; Ecevit, Mustafa Cenk; Sarıoğlu, Sülen; Sütay, Semih
Abstract : Ameloblastic fibroodontoma (AFO) is a rare entity of mixed odontogenic tumors and frequently arises from posterior portion of the maxilla or mandible in first two decades of life. Herein, a 35-year-old woman with a noncontributory medical history who presented with a progressive left maxillary toothache, left maxillary first molar tooth mobility, and swelling in the left maxillary molar area for the last 2 months was reported. Radiologically, a tumor that originated from periapical area of the second mature molar teeth of maxilla was seen and additively unerupted tooth was not detected. The histopathologic examination revealed AFO. The patient is disease-free for five years after treated with limited segmental alveolectomy combining with Caldwell-Luc procedure.